2016
DOI: 10.3389/fphar.2016.00023
|View full text |Cite
|
Sign up to set email alerts
|

The Trafficking of the Water Channel Aquaporin-2 in Renal Principal Cells—a Potential Target for Pharmacological Intervention in Cardiovascular Diseases

Abstract: Arginine-vasopressin (AVP) stimulates the redistribution of water channels, aquaporin-2 (AQP2) from intracellular vesicles into the plasma membrane of renal collecting duct principal cells. By this AVP directs 10% of the water reabsorption from the 170 L of primary urine that the human kidneys produce each day. This review discusses molecular mechanisms underlying the AVP-induced redistribution of AQP2; in particular, it provides an overview over the proteins participating in the control of its localization. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
52
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 403 publications
(286 reference statements)
0
52
0
Order By: Relevance
“…The clinical relevance of our findings is demonstrated by the fact that while in patients suffering from CDI the administration of dDAVP is the treatment of choice, it may be beneficial to administer as a supplementary therapy agents that are known to correct the AQP2 apical translocation defect such as statins or the JAK-2 and EFGR inhibitor AG-490 which both have been shown to be effective in Brattleboro rats. 35 This may indeed be an effective treatment strategy taking into account our findings that treatment of with dDAVP leads to increased AQP3 gene expression as well as protein levels in the plasma membrane of principal cells. So an approach that improves AQP2 and AQP3 turnover in the plasma membrane as suggested above, could prove beneficial to the clinical setting with respect to DI patients.…”
Section: Omcd Principal Cells Of Avp-deficient Brattleboro and Water-mentioning
confidence: 93%
“…The clinical relevance of our findings is demonstrated by the fact that while in patients suffering from CDI the administration of dDAVP is the treatment of choice, it may be beneficial to administer as a supplementary therapy agents that are known to correct the AQP2 apical translocation defect such as statins or the JAK-2 and EFGR inhibitor AG-490 which both have been shown to be effective in Brattleboro rats. 35 This may indeed be an effective treatment strategy taking into account our findings that treatment of with dDAVP leads to increased AQP3 gene expression as well as protein levels in the plasma membrane of principal cells. So an approach that improves AQP2 and AQP3 turnover in the plasma membrane as suggested above, could prove beneficial to the clinical setting with respect to DI patients.…”
Section: Omcd Principal Cells Of Avp-deficient Brattleboro and Water-mentioning
confidence: 93%
“…One of the main causes is long-term lithium treatment of bipolar disorders. This causes acquired NDI in up to 40% of the patients [18] .…”
Section: -Biologicals For Aquaporin Detection and Regulationmentioning
confidence: 99%
“…Several AQPs are implicated in other forms of edema (ocular edema, pulmonary edema, peripheral edema and systemic edema), and thus modulating aquaporin channel expression in mammals has been proposed to revert fluid accumulation associated with edema [65] . disorders that are not encompassed by the herein patent review can be found in [18] . blindness.…”
Section: -Biologicals For Aquaporin Detection and Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Vasopressin (VP)-mediated apical accumulation of aquaporin 2 (AQP2) is crucial for water reabsorption and urine concentration in the kidney collecting duct [1][2][3][4]. To initiate this process, VP induces changes in the phosphorylation state of AQP2 at several serine residues [5,6].…”
Section: Introductionmentioning
confidence: 99%